Early infection response of fungal biotroph Ustilago maydis in maize - Zou, Kunkun; Li, Yang; Zhang, Wenjie; Jia, Yunfeng; Wang, Yang; Ma, Yuting; Lv, Xiangling; Xuan, Yuanhu; Du, Wanli (Frontiers in Plant Science, 2022)
Common smut, caused by Ustilago maydis (DC.) Corda, is a destructive fungal disease of maize worldwide; it forms large tumors, reducing corn yield and quality. However, the molecular defense mechanism to common smut in maize remains unclear. The present study aimed to use a leading maize inbred line Ye478 to analyze the response to U. maydis inoculation. The histological and cytological analyses demonstrated that U. maydis grew gradually to the host cells 6 h post-inoculation (hpi). The samples collected at 0, 3, 6, and 12 hpi were analyzed to assess the maize transcriptomic changes in response to U. maydis. The results revealed differences in hormone signaling, glycometabolism, and photosynthesis after U. maydis infection; specific changes were detected in jasmonic acid (JA), salicylic acid (SA), ethylene (ET), and abscisic acid (ABA) signaling pathways, glycolysis/gluconeogenesis, and photosystems Ⅰ and Ⅱ, probably related to defense response. MapMan analysis demonstrated that the differentially expressed genes between the treatment and control groups were clustered into light reaction and photorespiration pathways. In addition, U. maydis inoculation induced chloroplast swelling and damage, suggesting a significant effect on the chloroplast activity and subsequent metabolic process, especially hexose metabolism. A further genetic study using wild-type and galactinol-sucrose galactosyltransferase (gsg) and yellow-green leaf-1 (ygl-1) mutants identified that these two U. maydis-induced genes negatively regulated defense against common smut in maize. Our measurements showed the pathogen early-invasion process, and the key pathways of both chlorophyll biosynthesis and sugar transportation were critical modified in the infected maize line, thereby throwing a light on the molecular mechanisms in the maize-U. maydis interaction.